Patterns of understory invasion in invasive timber stands of a tropical sky island. Issue 4 (13th April 2023) - Jobin, Varughese; Das, Arundhati; Harikrishnan, C. P.; Chanda, Ritobroto; Lawrence, Swapna; Robin, V. V.
Abstract: Current climate and land cover change threaten global mountaintops with increased spread of invasive species. Long‐established plantations of invasive trees on these mountaintops can alter their surroundings, further increasing invader‐facilitated invasion. Identifying the ecological conditions promoting such associations can help develop better management interventions. The Western Ghats's Shola Sky Islands (>1400 m MSL) host vast stretches of invasive tree plantations that sustain the colonization of other invasive woody, herbaceous, and fern species in their understories. Here, we analyzed vegetation and landscape variables from 232 systematically placed plots in randomly selected grids using non‐metric multidimensional scaling and Phi coefficient approaches to examine patterns of association (positive interactions) between understory invasive species with specific invasive overstory species. We also conducted GLMM with zero inflation to determine the influence of environmental variables where such associations occur. We find that understory invasion of multiple species under the canopy of other invasives is widespread across the Shola Sky Islands. Stands of Eucalyptus host the colonization of 70% of non‐native invasive species surveyed across the Shola Sky Islands. In particular, the Lantana camara invasion is strongly associated with Eucalyptus stands. We also found that climatic variables affect the colonization of understory woody invasive species, while invasion by exotic herbaceous species is associated with the density of road networks. Canopy cover impacts all invasives negatively, while fire incidence was negatively associated with invasion by Lantana spp. and the Pteridium spp. While the restoration of natural habitats primarily targets the highly invasive Acacia, less invasive Eucalyptus and Pinus are often not included. Our study suggests that retaining such invasive species in natural habitats, particularly protected areas, can hinder ongoing grassland restoration efforts by facilitating further invasions by multiple woody and herbaceous species. Abstract : Long‐established stands of invasive timber trees on mountaintops with unique natural habitats can increase invader‐facilitated invasion. The study identifies the ecological conditions that promote such specific associations and can help develop better management interventions.